New Methods for Imaging Evaluation of Chest Wall Deformities - Lain, Ana; Garcia, Laura; Gine, Carlos; Tiffet, Olivier; Lopez, Manuel (Frontiers in Pediatrics, 2017)
AIM: The purpose of this study is to describe the development of an external 3D scanner as a noninvasive method for imaging chest wall deformities. It allows objective assessment, reconstruction of the area of interest, and evaluation of the severity of the deformity by using external indexes. EXTERNAL 3D SCANNING SYSTEM: The OrtenBodyOne scanner (Orten, Lyon, France) uses depth sensors to scan the entire 3 dimensional (3D) external body surface of a patient. The depth sensors combine structured light with two classic computer vision techniques: depth from focus and depth from stereo. The data acquired are processed and analyzed using the Orten-Clinic software. MATERIALS AND METHODS: To investigate the performance of the device, a preliminary prospective study (January 2015-March 2016) was carried out in patients attending our hospital chest wall deformities unit. In total, 100 patients (children and young adults) with pectus excavatum or pectus carinatum, treated by surgery or nonoperative methods were included. In patients undergoing nonoperative treatment, external 3D scanning was performed monthly until complete correction was achieved. In surgically treated patients, scanning was done before and after surgical correction. In 42 patients, computed tomography was additionally performed and correlations between the Haller Index calculated by CT and the external Haller Index using external scanning were investigated using a Student test (r=0.83). CONCLUSIONS: External scanning is an effective, objective, radiation-free means to diagnose and follow-up patients with chest wall deformities. Externally measured indexes can be used to evaluate the severity of these conditions and the treatment outcomes.